Effects of yttria doping on some properties of YBa2Cu3O7-δ superconductor - Mustaffa Hj. Abdullah; Tan , Tuan Keat (Universiti Kebangsaan Malaysia, 1997)
Samples of Y-Ba-Cu-O superconductor with nominal compositions of YBa2Cu3O7-d + x (weight %) Y2O3 (x = 0 - 15) were prepared by solid state reaction method using the Y2Cu2O5 and BaCuO2 precursors as the starting reagents. The X-ray diffraction (XRD) diffractograms for the doped samples (x> 0) show an additional non-superconducting Y2BaCuO5 (211) phase. The scanning electron microscope (SEM) micrographs show that the smaller Y2BaCuO5 grains are precipitated on the surface of the larger YBa2Cu3O7-d (YBCO) crystals. The grain size of the YBCO decreases with increasing yttria. The superconducting zero resistivity critical temperature (Tco) of the doped samples is very close to the Tco of the YBCO for x < 5, but it seems to be significantly decreasing for larger x. The transport critical current density (J) for x < 5 is enhanced due to magnetic flux pinning process by the 211 phase. However, Jc decreased for larger x due to the increase of weak links at the grain boundaries of the YBCO phase.